Academic and Social Support Services for International Students: Current Practices - Martirosyan, Nara M.; Bustamante, Rebecca; Saxon, D. Patrick (Journal of International Students, 2019)
International students make valuable intellectual, cultural, and economic contributions to host-country colleges and universities. Some U.S. institutions enrolling greater numbers of international students offer a variety of specialized services designed to support students’ social adjustment, academic achievement, and language development in ways that potentially lead to greater retention and international student engagement. In this exploratory study, researchers analyzed website content to describe the types of support services offered by the top 20 U.S. universities with the greatest enrollment of international students in 2016. Implications are offered for U.S. higher education leaders interested in offering services to attract, support, and retain international students in an uncertain national political environment.